Threats of Human Exposure to Pathogenic Enterobacteria at Traditional Open Markets in Dar es Salaam, Tanzania (The Journal of Building and Land Development, 2020)
This study aimed at investigating occurrence and levels of indicator pathogenic microorganisms from traditional open markets (TOM) dealing with selling and slaughtering of live avian. Manzese and Buguruni TOM both in Dar es Salaam were selected as case study areas. The field survey revealed that the TOM receive over 60,000 avian per month from all regions of Tanzania and neighbouring countries out of which 52% are free-range kept indigenous chicken. Using biochemical test and a selective media, three Enterobacteria (E. coli, Klebsiella pneumonia and Salmonella) were identified and quantified following bacteriological analysis of soil, leachate and biowaste samples collected from both TOM. All samples showed high enterobacteria load >log1.0CFU/g. Leachate (pH 7.4) fromManzese TOM showed significant increase (p